Recent Progress in the Use of Cyanophosphates as Synthetic Intermediates - Harusawa, Shinya; Usami, Yoshihide (Synthesis, 2025)
The reaction of carbonyl compounds with diethyl phosphorocyanidate in the presence of a catalytic amount of lithium cyanide readily affords cyanophosphates (CPs), which have been utilized as useful intermediates for the introduction of a C1 unit in a variety of reactions. This short review summarizes the progress made in the application of CPs and the related compounds in organic synthesis over the last decade, in which the following items are covered. 1) Introduction. 2) Synthesis of Succinonitrile by Homocoupling from CPs with Cp2TiI. 3) Dearomative Allylation of Naphthaldehyde CPs by Palladium Catalysis. 4) Efficient Synthesis of a 5α-Reductase Inhibitor, 3-(Tetrazol-5-yl)-3,5-pregnadien-20-one through Allylic Rearrangement of CPs. 5) Generation of Alkylidene Carbenes through Tetrazole Fragmentation Derived from CPs. 6) Transformation of Benzaldehydes to Benzonitriles via CPs without One-Carbon Homologation. 7) Preparation of O-Phosphinoyl-protected Cyanohydrins by Aerobic Oxidation of α-Substituted Malononitriles. 8) Miscellaneous Reactions. 9) Summary and Perspective.
Keywords: Diethyl phosphorocyanidate; Cyanophosphates; Homocoupling; Dearomative allylation; 5α-Reductase inhibitor; Alkylidene carbenes; Benzonitriles